Employing Demand-Based Volumetric Forecasting to Identify Potential for and Roles of Devices in Scale-Up of Medical Male Circumcision in Zambia and Zimbabwe. (1st June 2016) - Fram, Francine; Church, Fred; Sundaram, Maaya; Sgaier, Sema K.; Ridzon, Renee; Eletskaya, Maria; Nanga, Alice; Gumede-Moyo, Sehlulekile; Tambatamba, Bushimbwa; Mugurungi, Owen; Ncube, Getrude; Xabayu, Sinokuthemba; et al.
Abstract : Introduction: Devices for male circumcision (MC) are becoming available in 14 priority countries where MC is being implemented for HIV prevention. Understanding potential impact on demand for services is one important programmatic consideration because countries determine whether to scale up devices within MC programs. Methods: A population-based survey measuring willingness to undergo MC, assuming availability of surgical MC and 3 devices, was conducted among 1250 uncircumcised men, ages 10–49 years in Zambia and 1000 uncircumcised men, ages 13–49 years in Zimbabwe. Simulated Test Market methodology was used to estimate incremental MC demand and the extent to which devices might be preferred over surgery, assuming availability of: surgical MC in both countries; the devices PrePex, ShangRing, and Unicirc in Zambia; and PrePex in Zimbabwe. Results: Modeled estimates indicate PrePex has the potential to provide an overall increase in MC demand ranging from an estimated 13%–50%, depending on country and WHO prequalification ages, replacing 11%–41% of surgical procedures. In Zambia, ShangRing could provide 8% overall increase, replacing 45% of surgical procedures, and Unicirc could provide 30% overall increase, replacing 85% of surgical procedures. Conclusions: In both countries, devices have potential to increase overall demand for MC, assuming wide scale awareness and availability of circumcision by the devices. With consideration for age and country, PrePex may provide the greatest potential increase in demand, followed by Unicirc (measured in Zambia only) and ShangRing (also Zambia only). These results inform one program dimension for decision making on potential device introduction strategies; however, they must be considered within the broader programmatic context.